1998
DOI: 10.4315/0362-028x-61.10.1363
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life of Sliced Raw Potatoes of Various Cultivar Varieties—Substitution of Bisulfites

Abstract: The effects of potato variety (Van Gogh, Bintje and Fambo), washing with browning prevention chemicals in place of sodium bisulfite, percentages of CO2, O2, and N2 in the package headspace, and storage time (1, 4, and 7 days) on the sensory and microbiological quality of potato slices were examined. Citric acid and ascorbic acid (at 0.1% each and at 0.5% each) were used as browning prevention chemicals. In the packaging atmosphere the percentage of N2 was 75 or 80%, the percentage of O2 was 5 or 0%, and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…This synergistic combination of AA + CIA with CA has been reported for various fresh-cut products (Laurila et al, 1998a;Gorny et al, 2002;He & Luo, 2007), but Jiang et al (2004) found that CIA alone retarded discolouration of cut water chestnut. SB was much better than AA + CIA as an anti-browning agent, a result consistent with many other reports (Gunes & Lee, 1997;Laurila et al, 1998b;Beltra´n et al, 2005). AA or ⁄ and CIA have been found effective to inhibit browning on cut potato in other studies (Ahvenainen et al, 1998;Rocha et al, 1998;Jiang et al, 2004;Limbo & Piergiovanni, 2006, but were ineffective in the present study on high browning potatoes.…”
Section: Effect Of Controlled Atmosphere and Anti-browning Chemicals supporting
confidence: 93%
See 4 more Smart Citations
“…This synergistic combination of AA + CIA with CA has been reported for various fresh-cut products (Laurila et al, 1998a;Gorny et al, 2002;He & Luo, 2007), but Jiang et al (2004) found that CIA alone retarded discolouration of cut water chestnut. SB was much better than AA + CIA as an anti-browning agent, a result consistent with many other reports (Gunes & Lee, 1997;Laurila et al, 1998b;Beltra´n et al, 2005). AA or ⁄ and CIA have been found effective to inhibit browning on cut potato in other studies (Ahvenainen et al, 1998;Rocha et al, 1998;Jiang et al, 2004;Limbo & Piergiovanni, 2006, but were ineffective in the present study on high browning potatoes.…”
Section: Effect Of Controlled Atmosphere and Anti-browning Chemicals supporting
confidence: 93%
“…An O 2 concentration as low as 0.3% would likely induce anaerobic metabolism (Mateos et al, 1993;Gorny et al, 2002;Ango´s et al, 2007). Laurila et al (1998b) found that modified atmospheres alone provided some benefit but did not completely maintain visual appearance of cut potato slices. The 3% O 2 + 12% CO 2 atmosphere was used in further testing because of the benefits noted and because it is an atmosphere that can be easily achieved with currently available plastic film packaging for fresh-cut products.…”
Section: Effect Of Controlled Atmospheres On Visual Quality and Colourmentioning
confidence: 97%
See 3 more Smart Citations